Germline Mutations in Patients With Early-Onset Prostate Cancer - Tang, Tang; Tan, Xintao; Wang, Ze; Wang, Shuo; Wang, Yapeng; Xu, Jing; Wei, Xiajie; Zhang, Dianzheng; Liu, Qiuli; Jiang, Jun (Frontiers in Oncology, 2022)
OBJECTIVE: To investigate the inherited mutations and their association with clinical features and treatment response in young-onset prostate cancer patients. METHOD: Targeted gene sequencing on 139 tumor susceptibility genes was conducted with a total of 24 patients diagnosed with PCa under the age of 63 years old. Meanwhile, the related clinical information of those patients is collected and analyzed. RESULTS: Sixty-two germline mutations in 45 genes were verified in 22 patients. BRCA2 (20.8%) and GJB2 (20.8%) were found to be the most frequently mutated, followed by CHEK2, BRCA1, PALB2, CDKN2A, HOXB13, PPM1D, and RECQL (8.3% of each, 2/24). Of note, 58.3% (14/24) patients carry germline mutations in DNA repair genes (DRGs). Four families with HRR (homologous recombination repair)-related gene mutations were described and analyzed in detail. Two patients with BRCA2 mutation responded well to the combined treatment of androgen deprivation therapy (ADT) and radiotherapy/chemotherapy. CONCLUSION: Mutations in DRGs are more prevalent in early-onset PCa with advanced clinical stages, and these patients had shorter progression-free survival. ADT Combined with either radiotherapy or chemotherapy may be effective in treating PCa caused by HRR-related gene mutations.